The Impact of the Covid-19 Pandemic on Implementation of Chemistry Practicum: A Case of SMAN 2 Seunagan - Gani, Abdul; Winarni, Sri; Hanum, Darmisah (FKIP Universitas Lampung, 2022)
Chemistry lessons that were previously conducted face-to-face must be changed to online methods during the covid-19 pandemic. This study aims to analyze the impact of the covid-19 pandemic on the implementation of chemistry practicum at SMAN 2 Seunagan. Data was collected using a questionnaire distributed to respondents. Data analysis was carried out using qualitative and quantitative descriptive techniques. This type of research is descriptive research with qualitative and quantitative approaches. The implementation of chemistry practicum refers to 3 components, namely: practicum support facilities, practicum activities and evaluation of practicum implementation. The population in this study were students with a sample of 36 people. The results showed that the implementation of chemistry practicum during the covid-19 pandemic was quite good, with a percentage of 38.9%. Thus, it can be concluded that the implementation of the chemistry practicum during the covid-19 pandemic has been running according to the goals and desired results.Keywords: Covid-19 pandemic, chemistry practicum, high school studentDOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1083-1092